Pengaruh Self-efficacy Terhadap Kemampuan Pemecahan Masalah Peserta Didik - Novita Sari, Relita; Nisa’, Roisatun (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research presents the results of the influence of self-efficacy on problem-solving abilities in the material Number Patterns and Object Configurations for YP Sunan Dalem Gumeno Gresik Middle School students. The subjects of this research were class VIII students with a total of 25 students consisting of 14 boys and 11 girls. Quantitative research methods are used as research methods. Questionnaires and problem-solving ability test questions were used as data collection techniques. The results of this research indicate that there is an influence of Self-efficacy on problem-solving abilities. This is proven by the results of the T-test analysis which shows a sig (2-tailed) value of 0.000 < 0.025 so it can be concluded that there is a significant difference between the average score of the Problem Solving Ability Test results for students with high self-efficacy and students with low self-efficacy.